2021
DOI: 10.1609/icwsm.v15i1.18065
|View full text |Cite
|
Sign up to set email alerts
|

Deception Detection in Group Video Conversations using Dynamic Interaction Networks

Abstract: Predicting groups of people who are jointly deceptive is critical in settings such as sales pitches and negotiations. Past work on deception in videos focuses on detecting single deceivers and uses facial or visual features only. We propose the concept of Face-to Face Interaction Networks (FFINs) and Negative Interaction Networks (NINs) to model interactions within a group of people. The use of FFINs and NINs in this paper enables us to leverage network relations in predicting face-to-face deception for the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…[7] illustrates a study in which a data-set containing conference videos was used to validate their semantic segmentation approach. Moving on to social interaction studies, [16] describes deception detection in group video conversations and points out the importance of considering such a kind of interaction, as video calls are becoming increasingly common after the Covid-19 hit. [3] recorded, through video-calls, conversations between children and their caregivers to investigate gaze, gesture, and facial expressions.…”
Section: Data-sets In the Age Of Covid-19mentioning
confidence: 99%
“…[7] illustrates a study in which a data-set containing conference videos was used to validate their semantic segmentation approach. Moving on to social interaction studies, [16] describes deception detection in group video conversations and points out the importance of considering such a kind of interaction, as video calls are becoming increasingly common after the Covid-19 hit. [3] recorded, through video-calls, conversations between children and their caregivers to investigate gaze, gesture, and facial expressions.…”
Section: Data-sets In the Age Of Covid-19mentioning
confidence: 99%
“…Some studies have found that facial micro-expressions such as protruding lips and symbolic gestures may be signs of lying [13,14]. Moreover, some researchers have detected lies by measuring cerebral blood flow using functional brain magnetic resonance imaging or by constructing a multichannel lie detection system based on cardiac impact signals [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…These resulted in development of new methods spanning robust detection and prediction models (He et al, 2021a;Mujumdar and Kumar, 2021;Oh et al, 2022b;Verma et al, 2022c), advance natural language processing and multimodality (Verma et al, 2022b,c), graphs (Raghavendra et al, 2022;Sharma et al, 2022), and recommender systems (Oh et al, 2021(Oh et al, , 2022aShalaby et al, 2022). The applications of these methods were in web integrity and led to new findings about online health misinformation (Micallef et al, 2020(Micallef et al, , 2022Verma et al, 2022a), counter-misinformation (Micallef et al, 2020;He et al, 2023;Ma et al, 2023), hate speech (He et al, 2021b), ban evaders (Niverthi et al, 2022), and digital deception (Glenski et al, 2020;Kumar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%